Family and polis: the socio-philosophical legacy of Plato and Aristotle at the present time = Famille et polis : Patrimoine sociophilosophique de Platon et d’Aristote à l’époque contemporaine = Famiglia e polis : Eredità socio-filosofica di Platone e di Aristotele nei tempi odierni - Dancák, Pavol (Philosophy & canon law, 2015)
The current debate on family is subject to rapid social changes which have had colossal negative impact on economy itself and on the economy of entire countries. The purpose of social and family life is not to bound, but to develop the human being. Thoughts about the future of the family are associated with education in the very sense that is pointed out by human experience. It can be said that Aristotle’s legacy is as follows: for subject, it is necessary to reflect pro futuro basic demand of how to be “together with others,” to act “with others” and, on which depends realization and completion of the subject’s being.